Perancangan Sistem Absensi Pegawai Menggunakan Layanan Lokasi GPS Pada Dinas Kominfo Kabupaten Serdang Bedagai - Ariyansah, Febri; Syukri, Khairiadi; Fikri Khair; Irwan (Jurnal Mahajana Informasi, 2024)
This study aims to design and develop an employee attendance information system using the Global Positioning System (GPS) Location Service at the Serdang Bedagai Regency Communication and Information Service based on the web. The problems identified are that it still uses a conventional system that requires the physical presence of employees and manual recording that is prone to errors and data loss. The purpose of this study is to improve the efficiency and accuracy of employee attendance management through the application of Global Positioning System (GPS) Location Service technology and a web-based system. The system implementation uses web technology and the Global Positioning System (GPS) Location Service. This system allows employees to clock in and out by obtaining accurate location information. The results of the implementation of this attendance system show advantages in the form of efficiency in the attendance process, increased accuracy of attendance data, and more flexible accessibility through the web interface. This study contributes to improving employee attendance management by utilizing GPS technology and a web-based system at the Serdang Bedagai Regency Communication and Information Service.